A Dynamic Travel Time Estimation Model Based on Connected Vehicles. (25th October 2015) - Tian, Daxin; Yuan, Yong; Qi, Honggang; Lu, Yingrong; Wang, Yunpeng; Xia, Haiying; He, Anping
Abstract : With advances in connected vehicle technology, dynamic vehicle route guidance models gradually become indispensable equipment for drivers. Traditional route guidance models are designed to direct a vehicle along the shortest path from the origin to the destination without considering the dynamic traffic information. In this paper a dynamic travel time estimation model is presented which can collect and distribute traffic data based on the connected vehicles. To estimate the real-time travel time more accurately, a road link dynamic dividing algorithm is proposed. The efficiency of the model is confirmed by simulations, and the experiment results prove the effectiveness of the travel time estimation method.